Prevalence of cervical cancer among village women: a study in an Upazilla Health Complex in Bangladesh - Abid, M. Taslima; Khatun, Nofisa; Kulsum, Umme; Razia, Sultana; Chowdhury, Akhtari Hossain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer arises when cells in the cervix undergo abnormal changes, leading to tumor formation. Although preventable, it remains the fourth most commonly diagnosed cancer and the leading cause of cancer-related deaths among women. This study aimed to assess the prevalence of cervical cancer among village women. Methods: This prospective observational study was conducted at Upazilla Health Complex (UHC), Sariakandi, Bogura, Bangladesh from January 2023 to December 2023. As the study subjects, a total of 1186 village women who participated in the cervical cancer screening program of the mentioned UHC were enrolled purposively. For data analysis, MS Office tools were applied. Results: In this study, the majority of participants belonged to the >40 years’ age group (53.2%), were housewives (73%), married at the age of 20 or younger (59%), and reported negative vaginal discharge (53%). Among the total participants, the prevalence of cervical cancer, as determined by visual inspection with acetic acid (VIA) tests, was found to be 1.18%. Conclusions: In comparison to other South Asian or African countries, the prevalence of cervical cancer among village women in Bangladesh is relatively low. However, housewives aged over 40 years, experiencing negative vaginal discharge, and marrying at age 20 or younger are particularly susceptible to such diseases here.